QuShape: Rapid, accurate, and best-practices quantification of nucleic acid probing information, resolved by capillary electrophoresis - Karabiber, Fethullah; McGinnis, Jennifer L.; Favorov, Oleg V.; Weeks, Kevin M. (COLD SPRING HARBOR LAB PRESS, PUBLICATIONS DEPT, 2013)
Chemical probing of RNA and DNA structure is a widely used and highly informative approach for examining nucleic acid structure and for evaluating interactions with protein and small-molecule ligands. Use of capillary electrophoresis to analyze chemical probing experiments yields hundreds of nucleotides of information per experiment and can be performed on automated instruments. Extraction of the information from capillary electrophoresis electropherograms is a computationally intensive multistep analytical process, and no current software provides rapid, automated, and accurate data analysis. To overcome this bottleneck, we developed a platform-independent, user-friendly software package, QuShape, that yields quantitatively accurate nucleotide reactivity information with minimal user supervision. QuShape incorporates newly developed algorithms for signal decay correction, alignment of time-varying signals within and across capillaries and relative to the RNA nucleotide sequence, and signal scaling across channels or experiments. An analysis-by-reference option enables multiple, related experiments to be fully analyzed in minutes. We illustrate the usefulness and robustness of QuShape by analysis of RNA SHAPE (selective 2'-hydroxyl acylation analyzed by primer extension) experiments.
Keywords: SHAPE; capillary electrophoresis; chemical probing; two-capillary; SELECTIVE 2'-HYDROXYL ACYLATION; RNA STRUCTURE-ANALYSIS; SECONDARY STRUCTURE; REACTIVITY; AUTOMATION; Biochemistry & Molecular Biology